Bibliometric Analysis of Global Trends in Parenting: Exploration of Digital Parenting, Emotion Regulation, and Parent Stress in The Era of Modern Technology - Arifurrohman (Journal of Psychological Insight, 2025)
Parenting practices are increasingly shaped by rapid technological development, raising new challenges for parental roles and well-being. This study aims to map global research trends in parenting by focusing on digital parenting, emotion regulation, and parental stress. Using a bibliometric research design, the study analyzes published scientific documents indexed in a central international database through keyword co-occurrence, citation, and collaboration analysis with the assistance of VOSviewer. The findings reveal a significant increase in parenting-related publications, with digital parenting emerging as a central theme, strongly linked to emotion regulation and parental stress clusters. Keyword network visualization shows dense interlinkages among technology use, emotional well-being, and stress management in parenting research, while collaboration patterns indicate uneven research distribution across regions. This study contributes a comprehensive thematic mapping that integrates technological, emotional, and psychological dimensions of parenting, offering a novel synthesis of fragmented research areas. The results imply the need for interdisciplinary and cross-cultural research collaboration to inform evidence-based parenting interventions and adaptive family support policies in the digital era.